Stressful situations and factors in students of nursing in clinical practice - Eliana Ofélia Llapa Rodrigues; Daniel Almeida Marques; David Lopes Neto; María José López Montesinos; Adriana Sousa Amado de Oliveira
Objective.To assess the risk factors for stress in undergraduate students of nursing in clinical practice in a public university in the Northeast region of Brazil. Methods. Cross-sectional descriptive study with 116 students from the fifth to the ninth period. The bilingual KEZKAK questionnaire, validated for Portuguese, was used. Stress was considered to be present when the score was equal or superior to 2. Results. The students with stress in clinical practice were 18 to 22 years old (2.82 ± 0.98), women (2.81 ± 0.96), married (2.80 ± 0.97), and who were permanent contracted employees (2.74 ± 0.94). The factors which were most associated with stress were: Lack of competence (2.99 ± 0.88); Impotence and uncertainty (2.98 ± 0.85); and Patients seeking a closer relationship (2.93 ± 1.01). The students of the sixth period were the most vulnerable to stress (2.85±0.96). Conclusion. The studies showed the main risk factors for stress among students of nursing in their clinical practice. These results could be used in the development of strategies seeking to reduce stress in this context as well as to contribute to promoting mental health.